Roman Cooking Wares Discovered at Sarmizegetusa Regia - Cristescu, Cătălin; Andreica, Gabriel (Rei Cretariae Romanae Fautorum Acta, 2022)
The ceramic evidence from Sarmizegetusa Regia comprises a relatively important number of Roman kitchen wares, discovered especially in the area of the stone fortress. They seem to belong to the so-called ‘legionary pottery’ and are represented by wheel-thrown cooking pots, lids and pans. Other recipients may be also ascertained to the Imperial ceramic production, as tableware, amphorae, turibula, mortaria, and even construction materials were unearthed during the excavations at Grădiștea de Munte. The cooking pots belong to archaeological contexts dated after the conquest of Sarmizegetusa Regia, at the beginning of the 2nd century. The vessel distribution reveals a concentration in the area of the fortification. Analogies are found in the province of Dacia and in the forts spreading on the Danube limes. We may presume that these cooking pots are linked to the presence of Roman legionary troops in the former capital of the Dacian Kingdom (epigraphic sources indicate the presence of soldiers from Legio IV Flavia Felix, Legio VI Ferrata and Legio II Adiutrix Pia Fidelis). The analysis of their fabric points to a local production for a part of the cooking pots and lids.